Estudo de coprólito da bacia sedimentar do Araripe por meios de espectroscopia FT-IR e difração de Raios-X - Lima, Ricardo Jorge Cruz; Freire, Paulo de Tarso Cavalcante; Sasaki, José Marcos; Saraiva, Antonio Álamo Feitosa; Lanfredi, Silvania [UNESP]; Nobre, Marcos Augusto de Lima [UNESP] (Sociedade Brasileira de Química, 2007)
Coprolites are fossilized faeces that constitute an important source of palaeobiological informations. This paper describes the characterization of some coprolite materials originated from the Romualdo Member of the Santana Formation (Araripe Basin, south of Ceará State in Brazil) by means of two techniques: X-ray powder diffraction and Fourier transform infrared spectroscopy (FT-IR). This characterization allowed us to determine the main composition of the coprolites, of the nodulus (where the coprolites were extracted) and of the sediment (where the nodulus was found) suggesting that the material was produced by a carnivorous fish of the Lower Cretaceous.
Study of coprolites from the Araripe sedimentary basin through FT-IR spectroscopy and x-ray diffraction
Keywords: coprolites; X-ray diffraction; Fourier transform infrared spectroscopy